The contributions of maternal oxytocin and maternal sensitivity to infant attachment security. Issue 4 (4th July 2022) - Kohlhoff, Jane; Karlov, Lisa; Dadds, Mark; Barnett, Bryanne; Silove, Derrick; Eapen, Valsamma
ABSTRACT: This study investigated links between maternal postnatal oxytocin, maternal sensitivity, and infant attachment security. At 3-months postpartum, participants (n=88) took part in a structured parent-infant interaction. Maternal oxytocin levels were assessed via blood, before and after the interaction. At 12-months postpartum, mother-child dyads completed the Strange Situation Procedure. Neither baseline oxytocin, oxytocin response, or maternal sensitivity were identified as significant independent predictors of infant attachment security or organisation. However, an interaction effect was identified, with higher maternal sensitivity being associated with secure infant attachment for mothers who showed an increase in oxytocin during parent–child interaction. Results indicate that maternal sensitivity, when accompanied by an increase in maternal oxytocin during parent–child interaction, is associated with the establishment of a positive early parent–child attachment relationship. This adds to the growing body of evidence highlighting maternal oxytocin response as a key adaptive process in the postpartum period.